The Lives of Girls and Young Women in the Time of COVID-19. Issue 3 (1st December 2020) - Mitchell, Claudia; Smith, Ann
Abstract : As with Zika, Ebola, HIV and AIDS, and other pandemics in recent history, girls and young women are particularly vulnerable to COVID-19 socially and emotionally if not medically. Some observers have referred to the current crisis as a tale of two pandemics in reference to both the obvious health issues and the pervasive gender inequalities that have become exacerbated, and others have referred to it as "the shadow pandemic" (UN Women 2020: n.p.) in highlighting the negative impact that physical distancing and social isolation are having on already vulnerable girls and young women experiencing sex- and gender-based violence. All over the world girls and young women are facing increasing levels of precariousness as a direct result of the health measures being taken to curb the global transmission of COVID-19. The increasing lack of privacy in the home furthers the practice of cultural forms of patriarchy that lead to violence.